Biodiversidad marina de Costa Rica: Gastrópodos (Mollusca: Gastropoda) de la costa Caribe - Rodríguez Sevilla, Leonora (2003)
Three hundred and eighty-four gastropod species from the Caribbean coast of Costa Rica are reported. Eight species are new records for Costa Rica: Cyclostrema tortuganum, Rissoina c.f. fenestrata, Vanikoro oxychone, Epitonium c.f. denticulatum, Latirus infundibulum, Hastula salleana, Daphnella lymneiformis and Tenaturris c.f. inepta. Thirteen species are found on the Caribbean and Pacific coasts of Costa Rica: Tegula fasciata, Cymatium nicobaricum, Anachis lyrata, Costoanachis varia, Mitrella ocellata, Agaronia testacea, Hastula cinerea, Architectonica nobilis, Dolabrifera dolabrifera, Stylocheilus striatus, Cavolinia longirostris, Phidiana lascrucensis and Spurilla neapolitana. In comparison with a recent report of the Caribbean and western Atlantic gastropods of Colombia, the Costarican fauna hardly presents 35.8% of those species. Similarly, in comparison with a work from Panama, the quantity of species shared between Costa Rica and its nearby country is 48.2%. The number of species reported here is probably an underestimation because few micromolluscs have been studied and no samples have been collected in deep waters nor in the north part of the coast.